PFAS, PCBs, PCDD/Fs, PAHs and extractable organic fluorine in bio-based fertilizers, amended soils and plants: Exposure assessment and temporal trends - Estoppey, Nicolas; Knight, Emma R.; Allan, Ian J.; Ndungu, Kuria; Slinde, Gøril Aasen; Rundberget, Jan Thomas; Ylivainio, Kari; Hernandez-Mora, Alicia; Sørmo, Erlend; Arp, Hans Peter H.; Cornelissen, Gerard (Elsevier, 2024)
Bio-based fertilizers (BBFs) produced from organic waste contribute to closed-loop nutrient cycles and circular agriculture. However, persistent organic contaminants, such as per- and poly-fluoroalkyl substances (PFAS), polychlorobiphenyls (PCBs), polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), as well as polyaromatic hydrocarbons (PAHs) can be present in organic waste or be formed during valorization processes. Consequently, these hazardous substances may be introduced into agricultural soils and the food chain via BBFs. This study assessed the exposure of 84 target substances and extractable organic fluorine (EOF) in 19 BBFs produced from different types of waste, including agricultural and food industrial waste, sewage sludge, and biowaste, and through various types of valorization methods, including hygienization at low temperatures (<150 °C) as well as pyrolysis and incineration at elevated temperatures (150–900 °C). The concentrations in BBFs (ΣPFOS & PFOA: <30 μg kg−1, Σ6PCBs: <15 μg kg−1, Σ11PAHs: <3 mg kg−1, Σ17PCDD/Fs: <4 ng TEQ kg−1) were found to be below the strictest thresholds used in individual EU countries, with only one exception (pyrolyzed sewage sludge, Σ11PAHs: 5.9 mg kg−1). Five BBFs produced from sewage sludge or chicken manure contained high concentrations of EOF (>140 μg kg−1), so monitoring of more PFAS is recommended. The calculated expected concentrations in soils after one BBF application (e.g. PFOS: <0.05 μg kg−1) fell below background contamination levels (PFOS: 2.7 μg kg−1) elsewhere in the literature. This was confirmed by the analysis of BBF-amended soils from field experiments (Finland and Austria). Studies on target legacy contaminants in sewage sludge were reviewed, indicating a general decreasing trend in concentration with an apparent half-life ranging from 4 (PFOS) to 9 (PCDD/Fs) years. Modelled cumulative concentrations of the target contaminants in agricultural soils indicated low long-term risks. Concentrations estimated and analyzed in cereal grains were low, indicating that exposure by cereal consumption is well below tolerable daily intakes.
Keywords: Circular economy; agriculture; soil pollution; accumulation